Evaluasi Fasilitas di Terminal Tipe A Entrop - Dessy Supusepa; Marsal Arung Lamba; Tommi Tommi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Terminals serve as transportation nodes that play a vital role in supporting community mobility and urban economic activities. As the capital city of Papua Province with a population of 420,577 inhabitants, Jayapura City requires an efficient transportation system to support increasingly dynamic social and economic activities. Entrop Terminal, as a Type A Terminal and the main transportation hub of Jayapura City, serves various transportation modes ranging from inter-city inter-provincial transport, cross-border transport, intra-provincial inter-city transport, urban transport, to rural transport. However, there is a significant problem where users prefer to wait for public transportation outside the terminal due to long queues inside the terminal, creating a shadow terminal phenomenon. This research aims to evaluate the facilities available at Entrop Type A Terminal in relation to the quality of services provided to users. This evaluation is important to identify facility and service deficiencies that cause users to be reluctant to use the terminal optimally. The research results are expected to provide recommendations for facility improvements and service quality enhancement at Entrop Terminal, so that it can function optimally as the main transportation hub and reduce the shadow terminal problems occurring in Jayapura City.